Electroanalytic evaluation of antagonistic effect of azole fungicides on Acinetobacter baumannii biofilms. (10th February 2022) - Olaifa, Kayode; Ajunwa, Obinna; Marsili, Enrico
Highlights: Two azole fungicides were repurposed against A. baumannii biofilm. At 1X MIC, itraconazole and ciprofloxacin inhibited 81.2% and 90.5% biofilm formation, respectively. At 1X MIC, itraconazole and ciprofloxacin decreased charge output at 48 h by 84.7% and 92.5%, respectively. Electroanalysis enabled non-destructive, real-time profiling of the antibiofilm activity. Abstract: Drug repurposing, which entails the use of established drugs to treat infections and ailments for which they were not originally developed for, is an immediate approach to fight antibiotic resistant pathogens. Antifungal drugs are good candidates for drug repurposing, due to their well-understood mechanism of action and low host toxicity. Acinetobacter baumannii is a common nosocomial pathogen with diverse virulence factors and broad-spectrum antibiotic resistance, resulting in high morbidity and mortality rates, especially as biofilm. Thus, repurposing of fungicides for control of A. baumannii biofilm is worth investigating. It is also pertinent to devise means for rapid characterization of antibiofilm effects of repurposed drugs. In this study, the activity of two antifungal drugs against A. baumannii biofilms is determined on screen-printed electrodes (SPE) through chronoamperometry. The tested fungicides – itraconazole and fluconazole - mitigated the formation of early A. baumannii biofilms, as determined by biochemical, electrochemical, and microscopic analysis. This work shows that bioelectrochemical methods can be used for continuous and non-destructive assessment of the antibiofilm activity of fungicides and provides the basis for implementation of bioelectrochemical methods in clinical antimicrobial testing. Graphical abstract: Image, graphical abstract